2021
DOI: 10.3390/su132212569
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Strategies to Improve the Corporate Social Responsibility Performance in Food and Pharmaceutical Industries: Empirical Evidence from Iran

Abstract: Since there is a lack of a strong CSR platform in the Iranian corporate environment, especially in the food and pharmaceutical industries, the proposed and existing strategies can be utilized to empower employees and the general public, improve executive processes, improve quality and customer satisfaction, and finally, organize financial and accounting reports. Hence, this study seeks to determine and evaluate strategies to improve the concepts and domain of corporate social responsibility (CSR) of food and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…The current CSR evaluation methods are mainly the Delphi method, principal component analysis, entropy value method, analytic hierarchy process (AHP), etc. [40][41][42]. The comparison of findings and limitations of different research methods is shown in Table 2.…”
Section: Evaluation Methodsmentioning
confidence: 99%
“…The current CSR evaluation methods are mainly the Delphi method, principal component analysis, entropy value method, analytic hierarchy process (AHP), etc. [40][41][42]. The comparison of findings and limitations of different research methods is shown in Table 2.…”
Section: Evaluation Methodsmentioning
confidence: 99%
“…In the relevant literature, the construction of core competitiveness of construction enterprises focuses on human capital, technological capital, and structural capital, while social capital is often ignored. In this case, this paper analyzes the core competitiveness of construction enterprises from the perspective of fulfilling their social responsibilities, accumulating social capital, and transforming knowledge capital, and tries to improve the research on the core competitiveness of construction enterprises [6].…”
Section: Introductionmentioning
confidence: 99%